THE DEVELOPMENT OF A ROTATION SURFACE GENERATED BY HYPOCYCLOID WITH 4 BRANCHES - Liliana LUCA (Fiabilitate şi Durabilitate, 2016)
This paper proposes a method for determining a development of the rotation surface, which is the rotation of hypocycloids with 4 branches. It has been chosen a four-cusped hypocycloid called astroid, because, due to its aesthetic shape, this could be used in industrial design. This paper proposes getting the development for a rotation surface generated by astroid. It is applied the graphical method of descriptive geometry by analogy with the developed by the sphere. This approximate graphical method is applied relatively simple and can be used when a high precision is not required for the product.